2017
DOI: 10.1016/j.chembiol.2017.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Polyubiquitin-Photoactivatable Crosslinking Reagents for Mapping Ubiquitin Interactome Identify Rpn1 as a Proteasome Ubiquitin-Associating Subunit

Abstract: SUMMARY Ubiquitin (Ub) signaling is a diverse group of processes controlled by covalent attachment of small protein Ub and the polyUb chains to a range of cellular protein targets. Best documented Ub signaling pathway is the one that delivers polyUb-proteins to the 26S proteasome for degradation. However, studies of molecular interactions involved in this process have been hampered by the transient and hydrophobic nature of these interactions and the lack of tools to study them. Here, we develop Ub-phototrap (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(77 citation statements)
references
References 112 publications
3
74
0
Order By: Relevance
“…One microgram of purified 26S proteasomes was used in an in vitro processing/degradation assay with 300 ng of purified His 6 -tagged conjugates in 40 μl reactions containing 25 mM Tris-HCl, pH 7.5, 10 mM MgCl 2 , 10% glycerol, 1 mM ATP, 1 mM DTT at 37 °C as described in ref. 66 . Reactions were stopped by the addition of 40 μl of 2× SDS Laemmli’s buffer and analysed by western blotting.…”
Section: Methodsmentioning
confidence: 99%
“…One microgram of purified 26S proteasomes was used in an in vitro processing/degradation assay with 300 ng of purified His 6 -tagged conjugates in 40 μl reactions containing 25 mM Tris-HCl, pH 7.5, 10 mM MgCl 2 , 10% glycerol, 1 mM ATP, 1 mM DTT at 37 °C as described in ref. 66 . Reactions were stopped by the addition of 40 μl of 2× SDS Laemmli’s buffer and analysed by western blotting.…”
Section: Methodsmentioning
confidence: 99%
“…Once photoactivated by UV, it is able to crosslink nearby proteins, thus stabilizing often very weak UBD:Ub interactions. By using Ub-PT as a tool, Chojnacki et al (2017) identified proteasomal subunit Rpn1 as a novel Ub receptor. Moreover, Ub-PT can have pLeu incorporated at multiple positions within Ub molecule, making it very useful for capturing UBDs that interact in different ways with Ub.…”
Section: Identification Of Novel Ubiquitin Readers and Determination mentioning
confidence: 99%
“…Ovaa et al introduced photoleucine containing a photocrosslinking group into the sequence of Ub through SPPS, and then enzymatically assembled it into a Ub chain to generate a photocrosslinking polyUb probe. 97 3.4.2.2 Insertion of unnatural amino acids. Virdee et al used an evolved engineered pair of tRNA and aminoacyl-tRNA synthetase to embed p-benzoyl-L-phenylalanine (Bpa) into the sequence of Ub.…”
Section: Incorporation Of Chemically Reactive Groupsmentioning
confidence: 99%
“…98 Meanwhile, Glickman et al developed photo-crosslinking polyUb probes for detecting proteasome subunits that interact with Ubs. 97 4.2.4 Monitoring changes of Ub chain conformation. Komander et al designed M1, K63 and K48 diUb probes containing a FRET dye pair.…”
Section: This Journal Is © the Royal Society Of Chemistry 2020mentioning
confidence: 99%